An effective metaheuristic for the robust distributed flowshop scheduling problem. Issue 1 (1st April 2022) - Guo, Hengwei; Sang, Hongyan; Sun, Xiaobin; Zhao, Yasheng; Tian, Mengxi; Li, Zhongkai
Abstract: This paper discusses the distributed permutation flowshop scheduling problem under uncertain processing time and considers the sequence-dependent setup times (denoted as DPFSP_UPT_SDST). Uncertain processing times are described by interval scenarios. An expectation-standard deviation robust model is used to describe the DPFSP_UPT_SDST. Based on the characteristics of the DPFSP_UPT_SDST, four heuristics are proposed. In addition, a discrete Fruit Fly optimization algorithm with an age mechanism is proposed, which helps the algorithm to avoid local optimum and increases the diversity of solutions. The parameters of the proposed algorithm are calibrated by a detailed design experiment. Finally, the effectiveness of the proposed heuristics and metaheuristic is demonstrated by a comprehensive comparison with the closely related and state-of-the-art algorithms.